IMF Staff papers : Volume 38 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1991)
The welfare effects of mitigating the costs of inflation are examined. In a model where money reduces transactions costs, a fall in inflation costs is equivalent to financial innovation. This can be caused by paying interest on deposits, indexing money, or 'dollarizing.' Results indicate that financial innovation raises welfare in low-inflation economies while reducing it in high-inflation economies because of the offsetting indirect effect of higher inflation to finance the budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet